La evaluación auténtica y la evaluación de destrezas con criterio de desempeño - Arízaga Huayllazaca, Marcos Emanuel (2021)
From this bibliographical research it is intended to emphasize the important role that evaluation plays in Ecuadorian education as a key piece that fills what is learned with meaning and usefulness, through the acquisition and mastery of skills by students. In this sense, this monograph focuses on exposing essential aspects of two evaluation categories: authentic evaluation and the evaluation of skills with performance criteria; For this, as a starting point, the historical aspect of the evaluation is analyzed, covering its chronology, meanings and characteristics according to the different pedagogical models; Likewise, the constructivist bases that configure what is understood by evaluation are made explicit, in accordance with the educational proposal of the Ecuadorian curriculum, organized in skills with constructivist overtones. Within the constructivist postulates of evaluation, authentic evaluation is conceived as a viable option to evaluate student performance, as it gives relevance to "know-how" within real-life contexts, through the implementation of a variety of evaluation techniques and instruments. Therefore, the authentic evaluation constitutes an optimal model to evaluate the skills with performance criteria, raised in the Ecuadorian educational program, since it harmoniously relates the "know-how" of the student with their close environment.